Impact of dosing regimen of custirsen, an antisense oligonucleotide, on safety, tolerability and cardiac repolarization in healthy subjects. (22nd June 2015) - Rabinovich‐Guilatt, Laura; Elgart, Anna; Erisson, Lavi; Willsie, Sandra K.; Tessler, Shoshi; Barnett‐Griness, Ofra; Pande, Amitkumar; Spiegelstein, Ofer
<x xml:space="preserve">Abstract</x> Aims Custirsen (OGX‐011/TV‐1011), a second‐generation antisense oligonucleotide (ASO) that reduces clusterin production, is under investigation with chemotherapy in patients with solid tumours. Custirsen is associated with constitutional symptoms (CS) that may interfere with clinical pharmacology investigations, such as QT interval studies. Experience with other ASOs suggests NSAID premedication may ameliorate CS, but we observed suboptimal outcomes in healthy subjects given custirsen and NSAIDs. We sought to establish a custirsen regimen for future clinical pharmacology studies in healthy subjects. Methods Subjects received custirsen (640 mg intravenously over 120 min) with dexamethasone premedication or increasing doses (320, 480, 640 mg over 6 days) of custirsen with dexamethasone premedication, then one full custirsen dose without premedication on day 8. Incidence/severity of adverse events (AEs) and extensive electrocardiogram readings were evaluated. Pharmacokinetic parameters were estimated. Results AEs included CS, elevated transaminases and prolonged activated partial thromboplastin time (aPTT) that were predominantly grade 1/2. Administration of increasing custirsen doses and dexamethasone premedication reduced the incidence of CS associated with full dose custirsen. Transaminase elevation showed a dose‐dependent effect (0% at days 2, 4, 27% at day 6) with the highest custirsen doses. Increasing doses of custirsen may have mitigated the severity but not incidence of aPTT prolongation. Neither regimen was associated with cardiac repolarization changes in QT values or concentration–effect analyses. The custirsen pharmacokinetic profile was consistent with previous experience. Conclusion Escalation of custirsen dose combined with dexamethasone premedication reduced CS associated with full dose custirsen and should be considered in future clinical pharmacology studies of custirsen.